The use of information on food labels: the consumers’ perspective in Malaysia - Kepal Nasir, Noreina; Mohd Jusoh, Nur Aniza Quantaniah; Ying, Tan Shoo (American Scientific Publishers, 2018)
The food industry in Malaysia is governed by Food Safety Act 1983 and Food Regulation 1985 in protecting the consumer rights especially when it comes to standards of safety, hygiene and quality. Consumers in Malaysia are increasingly conscious towards these standards and are moving towards making better choices in food consumption. In relation to this, the study explores five distinct factors that influence information usage on food labels among consumers. It also investigates the differences of information usage between genders. 322 responded to the distributed questionnaires were among shopping centre visitors in Shah Alam, Selangor. A descriptive analysis conducted and revealed that consumers use information on food label to avoid consuming certain substances. The inferential analysis showed that female used food labels more frequently than male.